Averting posthumous conflicts over inheritance: Takharuj negotiation - Sarumi, Isa Abdur-Razaq; Ansari, Abdul Haseeb; Mohd, Azizah; Ibrahim, Norliah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The principles of Islamic law of inheritance are more comprehensively explained in the primary source of the Islamic legislation than any other jurisprudential issues. The detailed explanation of the distribution to the surviving heirs prevents any probable conflict after the demise of the testator. However, the conflict sometimes arises not from the prescribed methods of distribution but from the estate, especially when it involves immovable properties. To avoid this conflict, Muslim scholars have provided a very comprehensive solution through the concept of Takharuj negotiation. This paper, therefore, seeks to explain the legal formwork for negotiation through Takharuj from the classical books of Islamic Law and Jurisprudence. The paper extensively discusses the legality of Takharuj and the processes of negotiation with typical examples of distribution of bequeath under the Islamic law of inheritance. The research adopts qualitative doctrinal approach by revisiting classical books. The paper finds that any posthumous conflicts can be avoided through takharuj negotiation.